RENEWABLE ENERGY TRANSITION AND ITS IMPACT ON ENVIRONMENTAL HEALTH AND AIR QUALITY IN URBAN AREAS OF BANTEN PROVINCE - Lani Febriani; Erwan Darmawan; Iwa Nugraha Wirawan Noerdin (INJOSEDU: International Journal of Social and Education, 2026)
The transition to renewable energy is one of the main strategies for reducing air pollution and improving environmental health in urban areas. Banten Province, as a region with high industrial and transportation activity, faces air quality issues that impact public health. This research aims to analyze the impact of the renewable energy transition on air quality and environmental health in urban areas of Banten Province. The research uses a quantitative approach with descriptive and explanatory designs. Data were obtained from secondary air quality data including parameters PM2.5, NOx, SO₂, CO, and O₃, as well as primary data from a community survey regarding environmental health conditions. Data analysis was performed using descriptive statistics and regression models to test the relationship between renewable energy use, emission reduction, and health impacts. The research results indicate that increased utilization of renewable energy significantly impacts the reduction of air pollutant concentrations. The decrease in air pollution quality is associated with a reduced risk of respiratory and cardiovascular diseases in urban populations. This research concludes that the transition to renewable energy plays an important role in improving air quality and environmental health in urban areas of Banten Province, and therefore needs to be supported by sustainable policies and implementation.